Nitrogen nutrition modulates oxidative stress and metabolite production in Hypericum perforatum - Kováčik, Jozef; Dresler, Sławomir; Peterková, Viera; Babula, Petr (Protoplasma, 2020)
Impact of various nitrate concentrations (14.12 mM, 3.53 mM, no nitrate) or ammonium presence (14.12 mM) on physiological and metabolic changes in Hypericum perforatum after 14 days of cultivation was monitored. Nitrate deficiency suppressed growth of shoots but stimulated root growth while ammonium suppressed root growth: concomitant changes of ascorbic acid and glutathione supported these growth changes, e.g., unaltered level in roots under nitrate deficiency but depleted in ammonium treatment. Soluble proteins and water content were more suppressed by nitrate deficiency but total ROS, nitric oxide formation, and antioxidative enzyme activities (APX and SOD) indicate higher sensitivity of plants to ammonium. Though both extreme treatments (NO3- deficiency or ammonium) stimulated accumulation of total soluble phenols and affected PAL activity (in comparison with full or 1/4× nitrate dose), major phenols (chlorogenic acid and three flavonoids) were elevated mainly by NO3- deficiency. At the level of specific metabolites, NO3- deficiency had stimulatory impact on pseudohypericin (but not hypericin) content while hyperforin decreased. Expression of earlier putative gene of hypericin biosynthesis (hyp-1) showed rather partial correlation with pseudohypericin amount. Data indicate that depletion of NO3- is useful to obtain Hypericum plants with higher amount of health-positive secondary metabolites.
Keywords: dusík; Phenols; Seedlings; Hypericum; semenáček; Oxidative Stress; oxidační stres; Fluorescence microscopy; Mineral nutrition; Antioxidants; Nitrogen; Secondary metabolites; třezalka